2020
DOI: 10.1186/s13071-020-04254-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of ascaridoid parasites from captive wild carnivores in China using ribosomal and mitochondrial sequences

Abstract: Background: Despite the public health importance of toxocariasis/toxascariasis, only a few species of these ascaridoid parasites from wild canine and feline carnivores have been studied at the molecular level so far. Poor understanding of diversity, host distribution and the potential (zoonotic) transmission of the ascaridoid species among wild animals negatively affects their surveillance and control in natural settings. In this study, we updated previous knowledge by profiling the genetic diversity and phylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…leonina from dogs and wolves clustered together (Kimura 2-parameter (K2P) barcode gap distance > 1.7%), while those from wild felids (K2P barcode gap distance of 3%) and red foxes (K2P barcode gap distance of 6.58%) formed two separate groups, suggesting the existence of three cryptic species within the complex. Interestingly, this research also pointed out that gene flow among wild felid isolates could be low ( Fogt-Wyrwas et al., 2019 ) as supported by complete sequences and partial cox 2 and nad 1 analyses ( Xie et al., 2020 ).…”
Section: Examples Of Cryptic Diversity In Parasites Of Human and Vete...mentioning
confidence: 51%
See 1 more Smart Citation
“…leonina from dogs and wolves clustered together (Kimura 2-parameter (K2P) barcode gap distance > 1.7%), while those from wild felids (K2P barcode gap distance of 3%) and red foxes (K2P barcode gap distance of 6.58%) formed two separate groups, suggesting the existence of three cryptic species within the complex. Interestingly, this research also pointed out that gene flow among wild felid isolates could be low ( Fogt-Wyrwas et al., 2019 ) as supported by complete sequences and partial cox 2 and nad 1 analyses ( Xie et al., 2020 ).…”
Section: Examples Of Cryptic Diversity In Parasites Of Human and Vete...mentioning
confidence: 51%
“…Several molecular studies have demonstrated the presence of cryptic species among Ta. leonina isolates, with apparent species delimitation according to host ( Song et al., 2015 ; Li et al., 2018 ; Fogt-Wyrwas et al., 2019 ; Jin et al., 2019 ; Xie et al., 2020 ). In a preliminary study, cox 1 was employed to determine the genetic relationship between Ta.…”
Section: Examples Of Cryptic Diversity In Parasites Of Human and Vete...mentioning
confidence: 99%
“…The solid black diamond represents the species in this study. Fogt-Wyrwas et al 2019;Xie et al 2020), suggesting at least two distinct subclades of T. leonina infecting these hosts and supporting that T. leonina represents a species complex. Furthermore, four T. leonina isolates of grouped together, regardless of isolate origins and hosts, and were more closely related to other species from the family Ascarididae than species of families Toxocaridae, Anisakidae, and Ascaridiidae, demonstrating phylogenetic stability of these paraphyletic groups characterized in this study.…”
Section: Mitogenome Announcementmentioning
confidence: 74%
“…Moreover, increased epidemiological evidences suggest that T. leonina is emerging as an underestimated zoonotic agent because of close relationships between humans and their pets (e.g. dogs and cats) and increased interactions between people and wildlife hosts in zoos (Robertson and Thompson 2002;Li et al 2007;Li et al 2008;Okulewicz et al 2012;Xie et al 2020). Such situations highlight the significance and necessity for diagnosis and identification of T. leonina.…”
Section: Mitogenome Announcementmentioning
confidence: 99%
See 1 more Smart Citation